2012
DOI: 10.1016/j.evolhumbehav.2012.05.006
|View full text |Cite
|
Sign up to set email alerts
|

A structure-based repertoire of manual gestures in wild chimpanzees: statistical analyses of a graded communication system

Abstract: Great ape gestural communication is considered important in understanding the evolution of human language as these share important features, namely, flexible and intentional signal use. Although gestural repertoires have been compiled for captive and wild primates, reports are largely qualitative. We quantify the morphological structure and variation of gestural signals identified in the repertoire of a community of wild chimpanzees. Gestures were classified on the basis of 29 morphological features, such as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
68
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(73 citation statements)
references
References 39 publications
2
68
0
Order By: Relevance
“…The vocal production described here meets one of the key criteria previously established for identifying intentional signal production in great ape gestural communication (e.g. Leavens et al 2005): social use of signals directed at specific recipients (Liebal et al 2004;Hobaiter & Byrne 2011;Roberts et al 2012). In light of this, a potential interpretation of our results is that, in both the vocal and gestural domains, communication in chimpanzees derives from an intentional system capable of generating voluntary and flexibly produced signals.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The vocal production described here meets one of the key criteria previously established for identifying intentional signal production in great ape gestural communication (e.g. Leavens et al 2005): social use of signals directed at specific recipients (Liebal et al 2004;Hobaiter & Byrne 2011;Roberts et al 2012). In light of this, a potential interpretation of our results is that, in both the vocal and gestural domains, communication in chimpanzees derives from an intentional system capable of generating voluntary and flexibly produced signals.…”
Section: Discussionsupporting
confidence: 71%
“…Individuals not only showed strongly selective calling behaviour, in which they only targeted socially important individuals, but callers additionally looked towards the intended recipient while calling. Although such visual monitoring of the audience during signalling has been taken as a marker of intentional signal production in gesture research (Leavens & Hopkins 1998;Hobaiter & Byrne 2011;Roberts et al 2012), in this study it is difficult to discriminate between audience monitoring during signalling and more simple orientation to the playback stimulus. Despite this, however, our results show that calls that function to refer to external entities can have highly specific social targets and can be recipient-directed acts, challenging the argument that primate vocalizations appear to be indiscriminately broadcast and that it may be difficult for callers to direct calls to specific individuals to the exclusion of others (Tomasello 2008).…”
Section: Discussionmentioning
confidence: 96%
“…(Bruner 1981 characterized by a lack of any limb injuries (Roberts et al 2012b). Additionally, ad libitum 145 data on adult non-focal subjects was collected (N = 7 subjects, N = 54 events).…”
mentioning
confidence: 99%
“…As a result, recorded repertoire sizes can vary dramatically, even within the same study group. For example, Hobaiter and Byrne (2011) discriminated more than 60 gestures in the Sonso chimpanzee community of Budongo Forest, Uganda, while Roberts et al (2012) only found half as many, a reflection of methodological differences. Hobaiter and Byrne (2011) have chosen the typical approach in gesture studies, which is to record any body or limb movement with no obvious physical effect, but then to exclude those that do not pass "strict criteria for intentionality" (Genty et al 2009), which typically leads to excluding around 50% of observations.…”
Section: Primate Communication and Human Languagementioning
confidence: 99%
“…The contentious point here is that the intentionality criteria used to exclude behaviour are all based on subjective observer judgements. Roberts et al's (2012) approach has been somewhat more objective in that the supposed gestural signals were identified by their physical structure before relating them to eliciting context and recipient responses, which resulted in a much smaller repertoire.…”
Section: Primate Communication and Human Languagementioning
confidence: 99%